The effect of different habitat conditions on temporal and spatial variation in selected population properties of the rare plant species Trollius europaeus L. - Kostrakiewicz-Gierałt, Kinga; Kozak, Maciej; Kozłowska-Kozak, Katarzyna (Biodiversity: Research and Conservation, 2015)
The investigations presented here were carried out in years 2013-14, in a Molinietum caeruleae meadow with interrupted plant cover caused by animal activity (patch I); abandoned Molinietum caeruleae meadows with untouched plant canopy, dominated by species with considerable height of the above-ground parts (patches II-VI); as well as the edge (patch VII) and the interior (patch VIII) of a birch woodlot. The height of standing vegetation and soil moisture increased in subsequent patches, whereas the light availability at ground level showed inverse tendency. The abundance of Trollius europaeus subpopulations in all studied patches was rather low. In patch I, juvenile individuals dominated, while in other stands - flowering adults prevailed. The lack of temporal variability in the number of basal leaves observed in patches III, IV, V, VI and VII might be due to lack of available area necessary for clonal proliferation of ramets, while the increase of basal leaves number in other sites might suggest unlimited iterative growth. The dimensions of basal leaves in consecutive years were constant in majority of subpopulations, while they showed strong spatial variability increasing gradually from patch I to patch VII and, subsequently, decreasing in patch VIII. The substantial dimensions of basal leaves may enable better light capture in sites with great level of lateral shade, while smaller dimensions in patches located within a woodlot may be due to shade from above created by trees. Lack of temporal variability and presence of substantial spatial variability in the number and height of generative stems, as well as flower production might enhance chances for successful pollination in a competitive environment. Significant changes of follicle number in time and space suggest successful process of pollination in all patches excluding patch VIII. The weak condition of the ramet clusters in patch I is not compensated by considerable seedling recruitment, whereas the satisfactory state of the ramet clusters in patches II-VIII may not suffice for the long-term maintenance of populations in colonized areas.